Feminisation of Teaching: Factors Affecting Low Male participation in Early Childhood Teaching at Private Schools in Pakistan - Sana Danish; Meher Saigol (Journal of Education and Educational Development, 2020)
This study was aimed atidentifying associated barriers to entry of male teachers into early childhood teaching and to understand the gender inequality and the shortage of male role models for early learners at private schools of Karachi.A qualitative research was conducted with phenomenology as the chosen inquiry method. A purposeful sampleof six in-service educators was selected from four private schools in Karachi two male post-secondary teachers, two female early childhood teachers and two private school female heads. The data were collected using three semi structured interviews one for each samplesubtype. The study revealed that the male teachers did not teach early learners at private schools due to poor pay;low male adult and child compatibility; the influence of gender stereotypes and societal norms on occupational choice and child safety concerns. To create gender neutrality of early childhood teachers, male participants expressed an interest to teach young learners if offered equitable pay and professional development opportunities, while female participants suggested increased pay and child protection policy implementation.
Keywords: early childhood education; feminisation; national education policy; private schools